Development and Validation of a Rapid and Efficient Method for Simultaneous Determination of Scopolin and Scopoletin in Convolvulus Species by Ultra-high-performance Liquid Chromatography-Tandem Mass Spectrometry - Al-Rifai, Asma'a; Aqel, Ahmad; Al-Saleem, Muneera (Current Pharmaceutical Analysis, 2020)
Background: Convolvulus species are extensively used in traditional medicines for the treatment of peptic ulcer diseases primarily associated with the presence of many bioactive compounds, such as coumarins. Methods: A validation and improvement of a rapid, sensitive and simple technique for bioactive compounds analysis of scopolin and scopoletin in Convolvulus pilosellifolius (CP) and Convolvulus austroaegyptiacus (CA) plant extracts using UHPLC-MS/MS were performed. Both plants extracts were subjected to high-resolution DART-ToF-MS technique for fast profiling of their constituents. Results: DART-ToF-MS spectra proved the presence of experimental mass at 193.05137 and 355.10371 m/z in the extract of CA plant and at 193.05084 and 355.10365 m/z in CP plant extract for scopolin and scopoletin compounds, respectively. The total chromatographic analysis time was less than 10 min with excellent resolution and negligible matrix effect. The validated parameter showed good linearity (R2 ≥0.998) over a wide concentration range of 0.05-10.0 μg mL-1 for both scopolin and scopoletin, detection limits of scopolin and scopoletin were 0.03 and 0.01 μg mL-1, respectively. The method also showed good intraday and interday precisions (RSD<4.33%). The recovery percentage values were between 97.04 and 99.97% at three added concentration limits. The highest content of scopolin (3.485 mg g-1) and scopoletin (0.795 mg g-1) was detected in CA ethanolic extract. The studied plants were finally compared with all previous reports in terms of scopolin and scopoletin content. Conclusion: The results indicate that the suggested method can be used for regular analysis of active compounds in medicinal plant extracts.
Keywords: plant extract